2012
DOI: 10.1007/s00128-012-0623-x
|View full text |Cite
|
Sign up to set email alerts
|

Total Mercury in Liver and Muscle Tissue of Two Coastal Sharks from the Northwest of Mexico

Abstract: Total mercury (THg) in liver and muscle of three costal sharks from Mexico were evaluated. The highest concentrations of THg in muscle tissue of juveniles were found in Sphyrna lewini (0.82 ± 0.33 mg kg(-1) wet basis). Rhizoprionodon longurio adults had the highest concentrations (0.92 ± 1.03 mg kg(-1)). THg concentrations in liver were low compared to those found in muscle tissue; higher levels were found in liver of juvenile S. lewini (0.250 ± 0.07 mg kg(-1)). Results showed that 35 % of muscle tissue sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 11 publications
3
5
0
Order By: Relevance
“…This finding is well illustrated by the strong associations between body length and muscle Hg concentrations that have been observed for several shark species (Turoczy et al 2000;Gelsleichter and Walker 2010;Storelli et al 2011;Hurtado-Banda et al 2012;Maz-Courrau et al 2012;Delshad et al 2012). In the current study, although all scalloped hammerhead sharks were juvenile with relatively low variation in body size, significant correlations were found between total length and weight and Hg concentration in muscle and liver, but it was found that Hg in muscle increased and Hg in liver decreased as total length and weight incremented.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This finding is well illustrated by the strong associations between body length and muscle Hg concentrations that have been observed for several shark species (Turoczy et al 2000;Gelsleichter and Walker 2010;Storelli et al 2011;Hurtado-Banda et al 2012;Maz-Courrau et al 2012;Delshad et al 2012). In the current study, although all scalloped hammerhead sharks were juvenile with relatively low variation in body size, significant correlations were found between total length and weight and Hg concentration in muscle and liver, but it was found that Hg in muscle increased and Hg in liver decreased as total length and weight incremented.…”
Section: Discussionsupporting
confidence: 57%
“…The scalloped hammerhead shark S. lewini makes an important contribution to Mexican fisheries along the Gulf of California (Bizarro et al 2009) and is highly consumed by the local population, because it is abundant and inexpensive (Cartamil et al 2011;Hurtado-Banda et al 2012). The organisms that occupy high trophic positions in marine ecosystems, such as tuna, billfishes, and sharks, are particularly exposed to toxic elements like Hg through food intake (Kojadinovic et al 2007;Damiano et al 2011;McMeans et al 2015).…”
mentioning
confidence: 98%
“…Concerning sex, no differences between Hg concentrations for both muscle and liver were observed between male and female juveniles from either Cabo Frio or Rio das Ostras, corroborating literature assessments of Hg concentrations for other Rhizoprionodon members (R. acutus) from South Africa (McKinney et al, 2016) and the Persian Gulf (Adel et al, 2017), as well as other sharks, such as the blue shark Prionace glauca and shortfin mako Isurus oxyrinchus, sampled from the NE Atlantic (Biton-Porsmoguer et al, 2018), and nine shark species sampled from the Florida Coast (Hueter et al, 1995). Thus, juvenile males and females were assessed together per location in further statistical analyses.…”
Section: Biometric Sharpnose Shark Datasupporting
confidence: 80%
“…Large size individuals of P. glauca had greater mercury and lead concentrations than small individuals. This is a well-documented process [12,13,20,[25][26][27][28][29][30][31][32][33][34] known as bioaccumulation [25,28,35]. The bioaccumulation process can take different pathways, one of which is through the diet (biomagnification).…”
Section: Discussionmentioning
confidence: 99%